mMaple: a photoconvertible fluorescent protein for use in multiple imaging modalities. - Ann L McEvoy; Hiofan Hoi; Mark Bates; Evgenia Platonova; Paula J Cranfill; Michelle A Baird; Michael W Davidson; Helge Ewers; Jan Liphardt; Robert E Campbell (PLoS ONE, 2012)
Recent advances in fluorescence microscopy have extended the spatial resolution to the nanometer scale. Here, we report an engineered photoconvertible fluorescent protein (pcFP) variant, designated as mMaple, that is suited for use in multiple conventional and super-resolution imaging modalities, specifically, widefield and confocal microscopy, structured illumination microscopy (SIM), and single-molecule localization microscopy. We demonstrate the versatility of mMaple by obtaining super-resolution images of protein organization in Escherichia coli and conventional fluorescence images of mammalian cells. Beneficial features of mMaple include high photostability of the green state when expressed in mammalian cells and high steady state intracellular protein concentration of functional protein when expressed in E. coli. mMaple thus enables both fast live-cell ensemble imaging and high precision single molecule localization for a single pcFP-containing construct.